Remarks on the Ceratocanthinae fauna of Guangxi (China) (Coleoptera: Scarabaeoidea: Hybosoridae) - Li, Zechuan; Ballerio, Alberto (Zootaxa, 2025)
The recent description of Cyphopisthes erlangshen Wang, 2025 from Guangxi (China) is discussed and Cyphopisthes dohertyi (Paulian, 1942) is recorded from Guangxi for the first time. The peculiar aedeagal morphology of that species is also described for the first time. The female of Madrasostes lini Wang, 2025 is described and the generic placement of the species is discussed.